Global Outcome Assessment Life-long after stroke in young adults initiative—the GOAL initiative: study protocol and rationale of a multicentre retrospective individual patient data meta-analysis. Issue 11 (14th November 2019) - Ekker, Merel S; Jacob, Mina A; van Dongen, Myrna ME; Aarnio, Karoliina; Annamalai, Arunkar K; Arauz, Antonio; Arnold, Marcel; Barboza, Miguel A; Bolognese, Manuel; Brouns, Raf; Chuluun, Batnairamdal; Chuluunbaatar, Enkhzaya; et al.
Abstract : Introduction: Worldwide, 2 million patients aged 18–50 years suffer a stroke each year, and this number is increasing. Knowledge about global distribution of risk factors and aetiologies, and information about prognosis and optimal secondary prevention in young stroke patients are limited. This limits evidence-based treatment and hampers the provision of appropriate information regarding the causes of stroke, risk factors and prognosis of young stroke patients. Methods and analysis: The Global Outcome Assessment Life-long after stroke in young adults (GOAL) initiative aims to perform a global individual patient data meta-analysis with existing data from young stroke cohorts worldwide. All patients aged 18–50 years with ischaemic stroke or intracerebral haemorrhage will be included. Outcomes will be the distribution of stroke aetiology and (vascular) risk factors, functional outcome after stroke, risk of recurrent vascular events and death and finally the use of secondary prevention. Subgroup analyses will be made based on age, gender, aetiology, ethnicity and climate of residence. Ethics and dissemination: Ethical approval for the GOAL study has already been obtained from the Medical Review Ethics Committee region Arnhem-Nijmegen. Additionally and when necessary, approval will also be obtained from national or local institutional review boards in the participating centres. When needed, a standardised data transfer agreement will be provided for participating centres. We plan dissemination of our results in peer-reviewed international scientific journals and through conference presentations. We expect that the results of this unique study will lead to better understanding of worldwide differences in risk factors, causes and outcome of young stroke patients.